Vibrational and Thermal Properties of Crystalline Topiramate - Sena, Diniz M. (2008)
Topiramate, a powerful anticonvulsant drug, was investigated by X-ray diffractometry, FT-Raman, FT-IR, TGA and DTA techniques as well as by DFT calculations. From this study it was possible to tentatively assign most of the normal vibrational modes of the crystal. Thermal analysis from room temperature to 900 degrees C shows that the material does not present any structural phase transition and that the decomposition occurs in a two-step exothermic process.